Quantification of nanomaterial bioconjugation based on electrophoretic mobility shift - Vaculovicova, Marketa; Adam, Vojtech; Kizek, Rene (Electrophoresis, 2015)
Electrophoretic mobility shift assay (EMSA) is a well-established technique to monitor interactions between biomolecules particularly DNA and proteins. Even though numerous variations of this method have been presented, challenges in the form of detection sensitivity and/or variations in the stability of the formed complex still remain. With advances in the area of nanomaterials improvements in EMSA have been also suggested. Recently, Zhang and Wang (Electrophoresis 2015, 36, 1011-1015) presented electrophoretic mobility shift method for determination of number of DNA molecules conjugated to quantum dots (QDs), which was further utilized for calculation of enzymatic activity, sequence specific DNA detection, and neutral molecule quantification.
Keywords: Nanoconjugates; retardační test; Protein; Electrophoretic Mobility Shift Assay; nanokonjugáty; kvantové tečky; Electrophoretic mobility shift assay; DNA; Quantum Dots; Quantum dots